Spotlight on Innovation Blockchain for Intellectual Property with Saga Arvidsdotter - Arvidsdotter, Saga (O'Reilly Media, Inc., 2020)
Blockchain is revolutionizing the world by removing middlemen and putting individuals, groups and things in direct contact. Global and trustless, blockchain forms the internet of value, compared to today's internet of data. Key properties of blockchain, like immutability, transparency, and decentralization, can solve the problem of digital identities, which can serve as a base for intellectual property. In this Spotlight on Innovation, find out how blockchain technology can facilitate different types of intellectual property-and transform your business. Artist and blockchain engineer Saga Arvidsdotter explains what blockchain is and discusses the important and varied perspectives you should be familiar with when designing blockchain technology, including philosophy, finance, game theory, and writing code like law. Recorded on October 9, 2019. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Innovation, you'll discover what successful companies have in common and how you can follow their lead with small practical steps to transform your organization and prepare for the Next Economy.